Phase Behaviour of Ternary System: Soybean Oil/Non-Ionic Surfactants/Deionized Water - Nadiah Abdul Rashid, Nur; B.H. Ahmad, Faujan; Salwa Abdul Gani, Siti; Safinar Ismail, Intan (Asian Journal of Chemistry, 2013)
Ternary phase diagrams of soybean oil with different types of non-ionic surfactants and deionized water were constructed in order to determine their phase behaviours. The five ternary phase diagrams constructed were: soybean oil/Tween 80/deionized water; soybean oil/Span 20/ deionized water; soybean oil/Cremophor EL/deionized water; soybean oil/Cremophor EL-Tween 80/deionized water and soybean oil/Cremophor EL-Span 20/deionized water. The regions observed from the diagrams were isotropic, homogenous, liquid crystalline, two-phase and multiphase. The area of isotropic and homogenous region increased with the increasing of hydrophilic-lipophilic balance value and also with the presence of co-surfactant. Among those five ternary phase diagrams obtained, the largest one-phase region can be found at the formulation of soybean oil/Cremophor EL-Span 20/deionized water. Cremophor EL has the highest hydrophilic-lipophilic balance value, followed by Tween 80 and Span 20. Larger one-phase region is beneficial because the stability of the components in the mixture is higher if compared to two and multiphase regions.